2005
DOI: 10.1111/j.1600-6143.2005.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure after Lung Transplantation: Incidence, Predictors and Impact on Perioperative Morbidity and Mortality

Abstract: The incidence, predictors and clinical significance of acute renal failure (ARF) after lung transplantation are not well described. We retrospectively collected data on 296 patients transplanted at our center be-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
5
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 53 publications
9
105
5
3
Order By: Relevance
“…A recent meta-analysis of these studies suggested that both ARDS and mechanical ventilation were associated with a 3-fold increase in the risk of AKI (46). Most of the studies included in this analysis were observational studies, however, and focused on specific populations such as trauma patients (27), lung transplant recipients (29), cancer patients (30), or patients with hepatic failure (32). Thus, the general applicability of their findings is unclear.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A recent meta-analysis of these studies suggested that both ARDS and mechanical ventilation were associated with a 3-fold increase in the risk of AKI (46). Most of the studies included in this analysis were observational studies, however, and focused on specific populations such as trauma patients (27), lung transplant recipients (29), cancer patients (30), or patients with hepatic failure (32). Thus, the general applicability of their findings is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Despite this large body of evidence suggesting an interaction between respiratory failure and AKI, few studies have evaluated the effect of respiratory failure on renal function by clearly assessing the time of mechanical ventilation initiation relative to the onset of AKI (27)(28)(29)(30)(31)(32). A recent meta-analysis of these studies suggested that both ARDS and mechanical ventilation were associated with a 3-fold increase in the risk of AKI (46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of recognizing pretransplantation renal function deficits is underscored by the observation that CKD before transplantation portends poor posttransplant survival. 10,15,22,23 Perioperative Renal Insults AKI during the peritransplantation period creates additional risk for posttransplantation CKD (Figure 1). Mechanisms during and after surgery that may precipitate AKI include hypotension and hypoperfusion, administration of nephrotoxic agents such as radiocontrast, sepsis, and aggressive diuresis.…”
Section: Triggering Insultmentioning
confidence: 99%